EXPERIMENTAL AND THEORETICAL STUDY OF MODULUS OF ELASTICITY ON RUBBERIZED CONCRETE - Emiroglu, Mehmet; Yildiz, Servet; Ozgan, Ercan (Gazi Univ, Fac Engineering Architecture, 2009)
In this study, fine and coarse rubber aggregates were produced for using in concrete. Rubber filled concretes have been produced by replacing the normal aggregates with rubber aggregates (5%, 10%, 15% and 20%) by volume respectively. Physical and mechanical properties of the produced rubber filled concretes have been determined. Beam specimens with 100 x 100 x 500 mm were prepared for the three point bending tests. The three point bending tests have conducted on these beam specimens and deflection amount of the beams during the test have been measured. By using the deflection values elasticity modulus of the produced specimens have been determined. Also, the elasticity modulus of the specimens has been calculated by using empirical equations which were proposed from some countries' standards. It was tried to determine that the relationship between the experimental results and empirical equation results for elasticity modulus. As a result, it is determined that while increasing rubber content in the concrete the relationship between experimental results and empirical equation results for elasticity modulus were decreased. However, it is observed that there was a high correlation between experimental results and empirical equation proposed by American Concrete Institute (ACI) for elasticity modulus.
Keywords: Rubber filled concrete; waste vehicle tires; modulus of elasticity